(untitled) (Fiep Bulletin - online, 2013)
The Pro-Culture Popular Program with an emphasis on the Folklore (P.C.P.F) is developed in a Laboratory program of Popular Cultures and Folklore in the Physical Education and Sports Institute at the University of the State of Rio de Janeiro. It is made up of an integrated nucleus of studies and body arts learning in the expectation of creating a space for constant and steady reflection on the Popular Culture. The program aims at endearing the knowledge, the beliefs, and the costumes that are so meaningful for the human behavior. The methodology of this project is based upon a guidance of an ethnographic nature, privileging a qualitative approach and being registered in the realm of content analysis. It is made up of a Program which deals with reflection and the intervention at the same time. Making up these processes is therefore, this Program’s biggest challenge.